Difference between effects of norms on academic achievement in the Hjalli movement compared with others coeducational schools - Hrönn Árnadóttir 1990- (2014)
Effects of single sex schooling on students academic achievement has been studied in previous years and prior studies have shown positive relationships between single sex schools and good student academic achievement. The Hjalli movement is the first and only single sex school in Iceland and therefore it was interesting to see what effect of norms in the schools had on academic achievement. The aim of this study was to compare norms in form of social capital, time spent with family, social support and school norms and see what effects they had on Icelandic and mathematic academic achievement among students in the Hjalli movement and compare those effects with others coeducational schools. It was hypothesized that because of shared norms, students in the Hjalli movement show better academic achievement compared to others coeducational schools. Data from the Icelandic Centre for Social Research and Analysis were used in present study and the sample includes students in fifth, sixth and seventh grade, aged 10-12 years in Icelandic secondary school (n = 2213). Results were that there were rather small difference between norms in the Hjalli – movement and others coeducational schools and their effect on academic achievement was small. Girls had better academic achievement compared to boys. Keywords: the Hjalli - movement, single-sex schools, coeducational schools, norms, academic achievement Áhrif kynjaskiptra skóla á námsárangur hafa verið skoðuð undanfarin á og hafa fyrri rannsóknir sýnt fram á jákvætt samband á milli kynjaskiptra skóla og góðan námsárangur. Hjallastefnan eru fyrstu og einu kynjaskiptu skólarnir á Íslandi og því var áhugavert að skoða hver áhrif gilda Hjallastefnunnar voru á námsárangur. Markmið þessarar rannsóknar var að bera saman gildi í formi félagsauðs, tíma sem eytt er með fjölskyldu, félagslegum stuðningi og skólagilda og skoða hvort þessi norm höfðu áhrif á námsárangur í íslensku og stærðfræði á meðal nemenda í Hjallastefnunni og bera áhrifin saman við blandaða skóla. Sett var fram ...